Factors associated with delayed reporting of babies for retinopathy of prematurity screening (Journal of National Institute of Ophthalmology, 2025)
Background: Retinopathy of prematurity is one of the leading causes of preventable infant blindness worldwide.  It may be prevented if at risk infants are screened before occurrence of advanced stages. Purpose: To evaluate the factors associated with delayed reporting of babies for retinopathy of prematurity screening. Method: This cross sectional study was conducted in the Department of Vitreo-retina and Pediatric ophthalmology department of National Institute of Ophthalmology and Hospital, Dhaka from December 2019 to October 2021. Total 138 premature babies of ≤34 weeks of gestational age and or  ≤1750 gm birth weight were purposively included in the study. Timely reporting was defined as babies come within 30 days of birth and delayed reporting was defined as babies come after 30 days of birth for retinopathy of prematurity screening. All the information was recorded in a pre-designed data collection sheet. Results: Among the 138 premature infants 93 (67.4%) babies had timely reporting and 45 (32.6%) babies had delayed reporting for retinopathy of prematurity screening. Majority (n=93, 67.4%) of the premature babies were male child. Out of 138 premature babies, 42 (30.4%) babies had developed retinopathy of prematurity (ROP). Among the 45 babies with delayed reporting, major causes for delay were babies advised for screening but the heath care worker did not mention the time, Parental negligence, Distance, Financial constraint, Nationwide lockdown due to covid-19 pandemic, no advise for screening and sickness of the baby. There was significant difference in the groups regarding maternal education (P